Urban Jamaican creole : variation in the mesolect - Patrick, Peter L. (Varieties of English around the world. General series ;, 1999)
A synchronic sociolinguistic study of Jamaican Creole (JC) as spoken in urban Kingston, this work uses variationist methods to closely investigate two key concepts of Atlantic Creole studies: the mesolect, and the creole continuum. One major concern is to describe how linguistic variation patterns with social influences. Is there a linguistic continuum? How does it correlate with social factors? The complex organization of an urbanizing Caribbean society and the highly variable nature of mesolectal speech norms and behavior present a challenge to sociolinguistic variation theory. The second chi.